Fungal nanotechnology - Fernandes, S. (2010)
Due to the outbreak of infectious diseases caused by different pathogenic microorganisms and the development of drug resistance, nanoscale materials have emerged up as novel antimicrobial agents and the well known activity of silver ions and silver-based compounds has promoted research in this field. For this reason, there is an essential need to develop environmentally benign procedures for synthesis of silver nanoparticles for commercialization purposes. In this study, silver nanoparticles were synthesised extracellularly from silver nitrate using the fungi supplied by Micoteca da Universidade do Minho (MUM) fungal culture collection, and the morphology of the nanoparticles was characterised The potential to manipulate key parameters, which control growth and other cellular activities, to achieve an optimised production of nanoparticles were also investigated. In addition, a preliminary study was performed to assess the anti-fungal silver nanoparticles activity against bacteria.